Rural And Nonrural Primary Care Physician Practices Increasingly Rely On Nurse Practitioners - Barnes, Hilary; Richards, Michael R.; McHugh, Matthew D.; Martsolf, Grant (Health Affairs, 2018)
The use of nurse practitioners (NPs) in primary care is one way to address growing patient demand and improve care delivery. However, little is known about trends in NP presence in primary care practices, or about how state policies such as scope-of-practice laws and expansion of eligibility for Medicaid may encourage or inhibit the use of NPs. We found increasing NP presence in both rural and nonrural primary care practices in the period 2008-16. At the end of the period, NPs constituted 25.2 percent of providers in rural and 23.0 percent in nonrural practices, compared to 17.6 percent and 15.9 percent, respectively, in 2008. States with full scope-of-practice laws had the highest NP presence, but the fastest growth occurred in states with reduced and restricted scopes of practice. State Medicaid expansion status was not associated with greater NP presence. Overall, primary care practices are embracing interdisciplinary provider configurations, and including NPs as providers can strengthen health care delivery.